Statistical analysis for malachite green removal using palm-kernel-shell-activated carbon - Kabbashi, Nassereldeen Ahmed; Daoud, Jamal Ibrahim; Jami, Mohammed Saedi (INSI Publications, 2011)
Malaysia is a country with luxurious agricultural resources. However, without proper management, the waste resulted from processing activities of these agricultural process will lead to a major waste problem. This study involved the utilization of the palm kernel shell (PKS) activated carbon by performing the decolorisation of malachite green color. The adsorption study was done using shake flask investigation. The result obtained showed that the best product of activated carbon, produced at 750°C at 90 minutes impregnated with K2 CO3 weight ratio of 1.0. This product was chosen because of cost factor and the percentage removal of MG was high 99.2%. From this study, the best candidate for adsorption of MG gives 121.416 mg/g adsorption rate. It is recommended for future study that detailed should be conducted on production of activated carbon to produce a larger surface area, this study should be extended on the method of application of Potassium Carbonate in enhancing the pore size of activated carbon, and this study should be continued for removal of other colors especially colors that are high toxicity.